Impact of multipoint pacing on projected battery longevity in cardiac resynchronization therapy. An IRON‐MPP study sub‐analysis. (5th November 2019) - Forleo, Giovanni B.; Gasperetti, Alessio; Ricciardi, Danilo; Curnis, Antonio; Bertaglia, Emanuele; Calò, Leonardo; Pignalberi, Carlo; Calzolari, Vittorio; Ribatti, Valentina; Lavalle, Carlo; Potenza, Domenico; Tondi, Lara; et al.
Abstract: Background: Multipoint pacing (MPP) may improve clinical outcomes in patients with cardiac resynchronization therapy defibrillators (CRT‐D), but its impact on battery longevity in a real‐world population has not been investigated in large trials. Objective: Compare projected battery longevity in CRT‐D patients with and without MPP during long‐term follow‐up. Methods: The Italian registry on multipoint left ventricular pacing (IRON‐MPP) is a prospective, multicenter registry of patients implanted with MPP‐capable CRT‐D devices. Projected battery longevity during follow‐up was compared for patients with MPP (MPP ON) vs single‐site (MPP OFF) left ventricular pacing at CRT‐D implantation. A sub‐analysis excluded crossover patients with MPP activation or deactivation occurring after implantation. A second sub‐analysis excluded patients with a right or left ventricular pacing amplitude >2.5 V. Results: Out of 237 CRT‐D patients (71 ± 9 years, 81% male) followed for 1.9 ± 0.8 years, 102 (43%) had MPP ON at implantation. Programmed atrial and ventricular outputs and percentage of pacing were similar between groups. MPP was associated with a 0.44 years reduction in projected battery longevity ( P  = .03) during long‐term follow‐up. Results were similar for the first and second sub‐analyses, with a 0.57 years ( P  < .001) and 0.71 years ( P  < .001) reduction in projected longevity, respectively. Conclusion: In this long‐term real‐world registry, early MPP activation is associated with less than a 1‐year reduction in projected battery life compared to single‐site biventricular pacing.